Estimating Short-Run Persistence in Mutual Fund Performance - Horst, Jenke ter; Verbeek, Marno (The Review of Economics and Statistics, 2000)
This paper analyzes the properties of a number of estimators that can be used to estimate short-run persistence in mutual fund returns. When data for different funds are pooled, it is advisable to correct for cross-sectional differences in expected returns. However, these adjustments may induce biases in the estimated persistence coefficients and thus lead to spurious persistence. Theoretical derivations, combined with a Monte Carlo study, show that these biases cannot be neglected for the samples that are typically used in applied work. We also estimate the short-run persistence in two samples of U.S. open-end mutual funds using quarterly returns for 1987–1994. An important conclusion is that the results are quite sensitive to the estimation method that is employed.